EXPLORING THE RELATIONSHIP BETWEEN MOBILE ADDICTION, INTERPERSONAL RELATIONSHIP, AND ACADEMIC BEHAVIOR AMONG YOUNG ADULTS IN TERTIARY INSTITUTIONS (Malaysian Journal of Learning and Instruction, 2021)
Purpose – Smartphones have become part and parcel of life in the 21st century.  Since there has been limited research exploring the relationship between mobile addiction, interpersonal relationship, and academic behaviour among young adults in tertiary institutions, the present study has embarked on an exploration of the relationship between these three variables in the Malaysian higher education context. Methodology – A descriptive correlational research design was employed to collect and analyse the data, which came from a total of 150 young adults who responded to an online Google form distributed through a WhatsApp link. The items in the questionnaire were adapted from various doctorate studies. The data were analysed using descriptive and inferential statistics such as the mean and standard deviation, correlation, and multiple regression. Findings – The study found that young adults in tertiary institutions in Malaysia experienced a case of moderate mobile addiction. The results also established that the three variables, namely mobile addiction, interpersonal relationship, and academic behaviour, were interrelated. The findings revealed that interpersonal relationship has positively contributed to the variance of academic behaviour, while mobile addiction has negatively impacted young adults’ academic behaviour in tertiary institutions.  Significance – The findings have provided valuable insights into how to help facilitate the monitoring of disruptive mobile usage among young adults in tertiary institutions.